Spin Transport in Organic Molecules - Guo, Lidan; Qin, Yang; Gu, Xianrong; Zhu, Xiangwei; Zhou, Qiong; Sun, Xiangnan (Frontiers in Chemistry, 2019)
Because of the considerable advantages of functional molecules as well as supramolecules, such as the low cost, light weight, flexibility, and large area preparation by solution method, molecular electronics has grown into an active and rapidly developing research field in the past decades. Beyond those well-known advantages, very long spin relaxation time of π-conjugated molecules due to the weak spin-orbit coupling facilitates a pioneering but fast-growing research field, named as molecular spintronics. Recently, a series of sustained progresses have been achieved with various π-conjugated molecular matrixes and spin transport is undoubtedly an important point for the spin physical process and multifunctional applications. Currently, most of the studies regarding spin transport are carried out with molecule-based spin valve, which shows a typical geometry that a thin-film molecular layer sandwiched between two ferromagnetic electrodes. In such a device, spin transport process has been demonstrated to have close correlation with spin relaxation time and charge carrier mobility of π-conjugated molecules. In this review, the recent advances regarding spin transport at these two aspects have been systematically summarized. Particularly, spin transport in those π-conjugated molecular materials considered to be very promise for spintronics development have also been highlighted, including molecular single crystal, cocrystal, solid solution as well as other highly ordered supramolecular structures.